AN ANALYSIS OF THE HEALTH CENTERS READINESS FOR ACCREDITATION IN BREBES DISTRICT IN 2018 - Lourina, Deny Ardi; Ayuningtyas, Dumilah (UI Scholars Hub, 2018)
The accreditation of health centers is an endeavor by the Ministry of Health to improve the quality and performance of health centers regulated by Permenkes No. 4/2015. Of the 38 health centers in Brebes, only 10 has been accredited. We wish to discover how prepared are the health centers to be accredited based on the resources available and pre-accreditation survey. Data was obtained through in-depth interviews and documentary research. Results indicated that there was sufficient funds, facilities and equipment for the accreditation. However, the assessment scores for human resources sufficiency and documentary completeness was low.